2022
DOI: 10.1111/bjhp.12626
|View full text |Cite
|
Sign up to set email alerts
|

The effects of social interactions on momentary stress and mood during COVID‐19 lockdowns

Abstract: OBJECTIVE: Social interactions are vital for our wellbeing, particularly during times of stress. However, previous studies linking social interactions to psychological outcomes during the COVID-19 pandemic have largely been retrospective and/or cross-sectional. Thus, we tested four preregistered hypotheses (H1-H4) concerning the real-time effect of social interactions on momentary changes in stress and mood during two COVID-19 lockdowns. DESIGN:We used an ecological momentary assessment approach in 732 partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
(69 reference statements)
1
6
0
Order By: Relevance
“…This finding suggests that social interactions may be most linked with subjective interpretations of our social state when they are most salient and necessary—when the social landscape is restricted by factors outside of people’s control. This finding complements other research that identifies mental health benefits to staying socially connected while physically isolated (Forbes et al, 2022; Nitschke et al, 2021; Sommerlad et al, 2022).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This finding suggests that social interactions may be most linked with subjective interpretations of our social state when they are most salient and necessary—when the social landscape is restricted by factors outside of people’s control. This finding complements other research that identifies mental health benefits to staying socially connected while physically isolated (Forbes et al, 2022; Nitschke et al, 2021; Sommerlad et al, 2022).…”
Section: Discussionsupporting
confidence: 85%
“…Alternatively, lockdown may exacerbate the impact of having social interactions on loneliness (Kuczynski et al, 2022), such that people benefit from social interaction most when they are isolated from others. Indeed, research points to the importance of staying socially connected while physically isolating: social interaction quantity and quality have been shown to predict better mental health outcomes during COVID-19 (Forbes et al, 2022; Nitschke et al, 2021; Sommerlad et al, 2022).…”
Section: Social Experiences During Covid-19mentioning
confidence: 99%
“…Finally, during COVID-19 lockdowns, one study [ 45 ] used EMA methods to investigate the impact of face-to-face social interactions on mood and stress in real time and found that having at least one social interaction preceding an assessment predicted a more positive mood, more calmness, heightened energetic arousal, and reduced stress compared to assessments when no social interactions were reported. These within-person effects persisted even while controlling for peoples’ moods and stress levels reported in the prior assessment, indicating that social interaction, and not pre-existing psychological states, were driving these effects.…”
Section: Psychological Statesmentioning
confidence: 99%
“…Likewise, by assessing participants three times per day for six days, researchers found that people felt more happiness and interest, and less sadness, tiredness, and pain, during assessments taken when they were engaged in a social interaction versus those taken when they were alone [44]. Finally, during COVID-19 lockdowns, [45] used EMA methods to investigate the impact of face-to-face social interactions on mood and stress in real-time and found that having at least one social interaction preceding an assessment predicted more positive mood, more calmness, heightened energetic arousal, and reduced stress compared to assessments when no social interactions were reported. These within-person effects persisted even while controlling for people's mood and stress levels reported in the previous assessment, indicating that social interaction, and not pre-existing psychological states, were driving these effects.…”
Section: Social Safetymentioning
confidence: 99%